Which is the simplified form of n Superscript negative 6 p cubed?StartFraction n Superscript 6 Over p cubed EndFraction
StartFraction 1 Over n Superscript 6 Baseline p cubed EndFraction
StartFraction p cubed Over n Superscript 6 EndFraction
n Superscript 6 Baseline p cubed

Answers

Answer 1
Answer:

Answer:

Third option. (p^3)/(n^(6))

Step-by-step explanation:

For this exercise you need to remember one of the properties for exponents.

There is a property called the "Negative property of exponents" which states the following:

b^(-n)=(1)/(b^n)

Where b \neq0

As you can observe,  b^n is the reciprocal of b^(-n)

In this case you have the following expression given in the exercise:

n^(-6)p^3

Observe the expression. As you can notice, the base "n" has a negative exponent, which is -6.

Therefore, applying the Negative property of exponents explained at the beginning of this explanation, you can simplify the expression.

Then, the simplified form of  n^(-6p^3) is the one shown below:

n^(-6)p^3=(p^3)/(n^(6))

Answer 2
Answer:

Answer:

C!

Step-by-step explanation:

it is


Related Questions

5 milligrams equals how many grams
Numbers that follow a rule
What is the lateral area of a rectangular prism with length of 4in width of 5in and height of 15in
A consumer survey was taken in a town with 18000 homes. Of the 360 homes surveyed, 48 had computers. On the basis of this survey, estimate the number of homes in the town they have computers.
Find examples of grocery store items newspaper,on television,on the Internet, or make it up. Compare unit prices of two different brands of the same item.Explain which item is a better buy.

5 times 7/8 then converted to simplest form?

Answers

5*7/8 = 4 3/8
5/1 * 7/8 = 35/8
convert into mixed number because numerator is bigger than the denominator so it it
4 3/8

What is the equation of the line that passes through the point 4,4 and has a slope of 0?

Answers

The equation of a line that passes through a point is an algebraic equation. It can also be referred to as the Slope-Intercept Equation.

The equation of the line that passes through the point (4, 4) and has a slope of 0 is written as: y = 4

The equation of the line through a point (x1, y1) can be represented by the algebraic equation:

y = mx + c

where:

m = slope

c = y - intercept

From the question,

(x1, y1) = (4, 4)

m = slope = 0

Substituting these values into the algebraic equation,

4 = (0 x 4) + c

 

Hence, y = 4

The equation of the line that passes through the point (4, 4) and has a slope of zero is y = 4

To learn more, visit the link below:

brainly.com/question/14045393

Answer:

y = 0x + 4 or y = 4.

Step-by-step explanation:

The slope is zero, and in other words, m = 0.

The slope intercept form is y = mx + b.

Replace m with 0.

y = 0m + b.

The y intercept is the y point on the line. Since this slope is a straight horizontal line, the y point given is the y intercept. b is the y intercept.

y = 0m + 4

Since any number times 0 is 0 you can right it as

y = 4.

This is the 2nd problem

Answers

x=4y+6\nx-3y=4\n\n4y+6-3y=4\ny=-2\n\nx=4\cdot(-2)+6\nx=-8+6\nx=-2\n\n\boxed{(x,y)=(-2,-2)}

What is 4 times 210 using distributive property

Answers

Answer:

I believe the answer would be 840

Step-by-step explanation:


Verify 2+2cot^2x=2cotxsecxcscx

Answers

2+2\cot^2x=2\cot x\sec x\csc x\n\nL=2(1+\cot^2x)=2\left(1+(\cos^2x)/(\sin^2x)\right)=2\left((\sin^2x)/(\sin^2x)+(\cos^2x)/(\sin^2x)\right)\n\n=2\left((\sin^2x+\cos^2x)/(\sin^2x)\right)=2\left((1)/(\sin^2x)\right)=(2)/(\sin^2x)\n\nR=2\left((\cos x)/(\sin x)\right)\left((1)/(\cos x)\right)\left((1)/(\sin x)\right)=2\left((1)/(\sin x)\right)\left((1)/(1)\right)\left((1)/(\sin x)\right)\n\n=2\left((1)/(\sin^2x)\right)=(2)/(\sin^2x)

\boxed{L=R}

Used:\n\n\cot x=(\cos x)/(\sin x)\n\n\sin^2x+\cos^2x=1\n\n\sec x=(1)/(\cos x)\n\n\csc x=(1)/(\sin x)

Please Solve:Adding and Subtracting PolymonialsAdd:  (–6 – n + 2n2) + (8 – 3n – 10n2)   
A.
–2 – 4n – 8n2
  
B.
2 – 2n – 8n2
  
C.
2 – 4n – 8n2
  
D.
–2 – 2n – 8n2

Add:  (8x + 2y – 3z – 4) + (–4x – 5y + 4z + 6)  
A.
–4x + 3y – z + 2
  
B.
4x – 3y – z + 2
  
C.
–4x + 3y –z – 2
  
D.
4x – 3y + z + 2

Subtract and simplify: (2p^2q – 3pq^2 + q^3) – (p^2q + q^3)  
A.
p^2q – 3pq^2
  
B.
2p^2q – 3pq^2
  
C.
p^2q – 3pq^2+2q^3
  
D.
p^2q – 2pq^2


Subtract and simplify: (–y^2 – 3y – 5) – (–3y^2 – 7y + 4)  
A.
2y^2 – 10y + 4
  
B.
2y^2 + 4y – 9
  
C.
–2y^2 – 10y – 1
  
D.
2y^2 – 7y – 9


Subtract and simplify: (10x^4 – 2x + 7) – (6x^4 + 2x^3 – 4x^– 1) 
A.
4x^4 – 2x^+ 4x^2 – 2x + 6
  
B.
4x^4 + 2x^– 4x^2 – 2x + 8
  
C.
4x^4 – 2x^+ 4x^2 – 2x + 8
  
D.
16x^4 + 2x^+ 4x^2 – 2x + 8

Answers

Add:\n \n (-6-n + 2n^2) + (8 - 3n - 10n^2) =\n \n= -6-n + 2n^2 + 8 - 3n - 10n^2 =\n \n=2 - 4n -8n^2 \n \n Answer : \ C. \ \ \2 - 4n - 8n2


Add: \n \n (8x + 2y - 3z -4) + (-4x - 5y + 4z + 6) = \n \n =8x + 2y - 3z -4 -4x - 5y + 4z + 6=\n \n=4 x - 3 y + z + 2 \n \n Answer : \ D. \ \ \ 4x - 3y + z + 2


Subtract \ and \ simplify: \n\n (2p^2q - 3pq^2 + q^3) -(p^2q + q^3)=\n \n= 2p^2q - 3pq^2 + q^3 - p^2q -q^3 = \n \n= p^2q - 3pq^2 \n \n Answer : \ A. \ \ \ \ p^2q - 3pq^2


Subtract \ and \ simplify: \n\n (-y^2 - 3y-5) - (-3y^2 - 7y + 4)= \n \n= -y^2 - 3y-5+3y^2 +7y- 4 =\n \n=2y^2+4y-9 \n \nAnswer : \ B.\ \ \ \ 2y^2 + 4y - 9


Subtract \ and \ simplify: \n\n (10x^4 -2x + 7)-(6x^4 + 2x^3 -4x^2 - 1) = \n \n = 10x^4 -2x + 7 - 6x^4 - 2x^3 +4x^2 + 1=\n \n=4x^4 -2x^3 +4x^2-2x + 8 \n \nAnswer : \ C. \ \ \ \4x^4 -2x^3 + 4x^2- 2x + 8
 

1)\n(-6-n + 2n^2) + (8-3n-10n^2) =2-4n-8n^2\ \ \ \Rightarrow\ \ \ Ans.\ C\n\n2)\n(8x+2y-3z-4)+(-4x-5y+4z+6)=4x-3y+z+2\ \Rightarrow\ Ans.D\n\n3)\n(2p^2q-3pq^2+q^3)-(p^2q + q^3) =p^2q-3pq^2\ \ \ \Rightarrow\ \ \ Ans.\ A\n\n4)\n (-y^2-3y-5)-(-3y^2-7y + 4) =-y^2-3y-5+3y^2+7y - 4=\n.\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ =2y^2+4y-9\ \ \ \Rightarrow\ \ \ Ans.\ B\n

5)\n(10x^4-2x + 7)-(6x^4 + 2x^3-4x^2-1) =\n=10x^4-2x + 7-6x^4 - 2x^3+4x^2+1=\n=4x^4-2x^3+4x^2-2x+8\ \ \ \Rightarrow\ \ \ Ans.\ C